The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments. (17th October 2019) - Cai, Chuang; Li, Gang; Di, Lijun; Ding, Yunjie; Fu, Lin; Guo, Xuanhe; Struik, Paul C.; Pan, Genxing; Li, Haozheng; Chen, Weiping; Luo, Weihong; Yin, Xinyou
Abstract: Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO2 enrichment (T‐FACE) systems. Parameters of a biochemical C3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering. Abstract : How photosynthesis acclimates to seasonal temperature changes under future climate conditions is unclear. We measured leaf photosynthesis of wheat and rice grown under T‐FACE with four combinations of two levels of CO2 and two levels of canopy temperature. Parameters of leaf photosynthesis and CO2 ‐diffusion conductance models were estimated for the four conditions and for several crop stages. Some model parameters showed seasonal temperature acclimation in both crops. However, crop models that ignored the acclimation effect did not make critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.